Large Engineering Systems : Proceedings of the International Symposium Held at the University of Manitoba, Winnipeg, Manitoba, Canada August 9-12, 1976. - Wexler, Alvin (Pergamon Press, 1977)
Large Engineering Systems documents the proceedings of the International Symposium held at the University of Manitoba, Canada on August 9-12, 1976. This book compiles papers on the technology of large engineering systems. The topics discussed include the analysis of an automobile body by finite element method; finite-element solution of boundary integral equations; optimum design of stiffened plate girders; and tuning of miniaturized analog hybrid circuits. The sparsity in large systems and trans-shipment problems; finite difference method with graded lattices; Kron's multidimensional electrom.